Analisis Pengaruh Jumlah Variasi Katalis MeOH Pada Pembuatan Biodiesel Melalui Proses Transesterifikasi - Harmiansyah; Efendi, Rustam; Muslimah, Siti; Hikmawati, Meli; Apriani, Santi; Simbolon, Sinober; Setiawan, Wahyu (Jurnal ELEMENTER (Elektro dan Mesin Terapan), 2023)
Biodiesel is a bioenergy or biofuel produced by transesterification of vegetable oil (animal fat). Transesterification is a chemical method in which oil triglycerides react with methanol with the help of an alkaline catalyst to produce biodiesel. The goal of this study is to determine the quality of biodiesel utilizing MeOH as a catalyst throughout the transesterification process. This study aims to produce biodiesel using the transesterification process with palm oil as the main raw material. Making biodiesel begins with heating the palm oil at 61-65 oC and then adding a mixture of NaOH and methanol solutions so that glycerol, emulsion, and biodiesel are obtained as a result of transesterification. Finally, a separatory funnel is used to obtain pure biodiesel. The yield values of biodiesel produced with MeOH catalysts of 20%, 25%, and 30% were 81.5%, 86.6%, and 44.4%, respectively. Furthermore, this study performed density calculations that influenced the quality of biodiesel from each amount of MeOH utilized to achieve a density of 0.85 g/ml. As can be observed, the usage of MeOH catalyst has an effect on the quality of biodiesel yields.